Strategy and Decision Making in Karate - Frigout, Jérôme; Tasseel-Ponche, Sophie; Delafontaine, Arnaud (Frontiers in Psychology, 2020)
Karate will be included to the events at the 2020 Summer Olympics in Tokyo, as an additional sport. The inner logic of this activity contains a specific scoring system and modelling. Three hundred nine bouts have been observed in competition context and result in new perspectives for training, and competing. The scoring of punches (43,7% of total scored points) and face kicks (37,9%) appears to be more significant (p≤0.01) than those of body kicks (15,3%, p≤0.01) and leg-sweeping (3,1%, p=0.31). Considering penalties, they do appear as very significant and associated to victory, when “scored” by the competitor against himself (p≤0.01). Competitors must score points and penalties. This zero-sum game imposes a simple rivalry with a search for domination, and must rely on a predefined strategy, as well as on initiative. Karatekas have to make-decision, such as when taking the risk of scoring points, penalties, weither they lead the score, or not. They may decide to expose or protect themselves, to create situations, or simply remain realist and stick to the plan. The question of decision-making, which is central here, forces us to place at the heart of our future works the notions of expectations and of self-fulfilling prophecy.